2011
DOI: 10.3201/eid1704.101115
|View full text |Cite
|
Sign up to set email alerts
|

Carriage ofStreptococcus pneumoniae3 Years after Start of Vaccination Program, the Netherlands

Abstract: To evaluate the effectiveness of the 7-valent pneumococcal conjugate vaccine (PCV7) program, we conducted a cross-sectional observational study on nasopharyngeal carriage of Streptococcus pneumoniae 3 years after implementation of the program in the Netherlands. We compared pneumococcal serotypes in 329 prebooster 11-month-old children, 330 fully vaccinated 24-month-old children, and 324 parents with age-matched pre-PCV7 (unvaccinated) controls (ages 12 and 24 months, n = 319 and n = 321, respectively) and 296… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 38 publications
7
59
1
Order By: Relevance
“…Each of these studies demonstrated that the carriage of VT serotypes decreased but resulted in increased non-VT serotype carriage, particularly serotype 19A; overall NP carriage did not change. These findings were supported by a recent systematic review of clinical trials assessing SPNP carriage [8][9][10][11]. However, the number of clinical trials assessing PCV13 effectiveness against SPNP carriage was small.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these studies demonstrated that the carriage of VT serotypes decreased but resulted in increased non-VT serotype carriage, particularly serotype 19A; overall NP carriage did not change. These findings were supported by a recent systematic review of clinical trials assessing SPNP carriage [8][9][10][11]. However, the number of clinical trials assessing PCV13 effectiveness against SPNP carriage was small.…”
Section: Discussionmentioning
confidence: 99%
“…Following the widespread use of pneumococcal conjugate vaccines, serotype 11A has become one of the most prevalent serotypes among pneumococci isolated from the nasopharynx (16)(17)(18) and, in one U.S. multicenter study, isolated from invasive disease (19). It can be postulated that pneumococci expressing serotypes 11A and 11E have contributed equally to the increase in "serotype 11A" prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two isolates [4% (2-6)] were resistant to erythromycin. Coresistance to erythromycin, clindamycin and tetracycline was found in 18 isolates [3% (2)(3)(4)(5)(6)]. These coresistant isolates belonged to ST/serotypes ST179/19F, ST63/15A, ST344/NT and ST4310/6C.…”
Section: The 2013 Sample (Pcv13 Era)mentioning
confidence: 99%